Teaching Real Analysis in Teacher Preparation Program through Content Bridging Strategy - Chhetri, Deb Bahadur (Janabhawana Research Journal, 2023)
This study aims to investigate the impact of content bridging, based on the ARCS Model of Instructional Design, on student motivation in learning Real analysis within a teacher preparation program at the bachelor’s level. The strategy aims to establish connections between Real analysis and secondary-level mathematics, emphasizing the relevance and applicability of the subject. The study employed a participatory action research approach, employing content bridging and observing the students’ behaviour during the instruction to study the change. The results indicate remarkable improvements in student behaviour, engagement, and active participation. Students exhibited increased motivation, completed assigned work, posed thoughtful questions, and demonstrated enthusiasm during class. These findings highlight the effectiveness of the content bridging in enhancing student motivation and understanding of Real analysis within the context of teacher preparation programs.